Midwifery Care for Primigravida with Hypertension Using Meniran Leaf Decoction at PMB Rismala, Asahan Regency - Bayu Larasati Wulandari; Reby Ulan Sri Zinta; Siti Zubaidah Br. Simangunsong (Sean Institute, 2025)
Hypertension in pregnancy (HDK) is the leading cause of maternal morbidity and mortality in Indonesia. Meniran leaves (Phyllanthus niruri) contain active substances such as filanthin, potassium, and flavonoids that function as natural vasodilators to lower blood pressure. Objective: To determine the effect of meniran leaf decoction on blood pressure reduction in pregnant women with hypertension at PMB Bd. Rismala Siagian. Methods: A descriptive case study was conducted on Mrs. S (23 years old, G1P0A0) with an initial blood pressure of 150/90 mmHg. The intervention consisted of administering 200 mL of boiled meniran leaf water twice daily for 7 days. Data was collected using observation sheets and a blood pressure monitor. Results: After seven days of intervention, the subject's blood pressure decreased significantly to 125/80 mmHg. Subjective complaints of dizziness, nausea, and leg edema were also reported to have disappeared. The potassium content in meniran helps regulate electrolyte balance and reduces fluid retention that triggers an increase in blood pressure. Conclusion: Meniran leaf decoction has been proven to be effective and safe for use as a non-pharmacological complementary therapy in midwifery care to reduce mild hypertension in pregnant women.